Analisis Strategi Komunikasi dalam Meningkatkan Kinerja Aparatur Desa di Desa Ciburuy Kecamatan Padalarang Kabupaten Bandung Barat - Khoerunisa, Fahra; Makmur (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the communication strategies implemented in improving the performance of village officials in Ciburuy Village. Effective communication is very important in village governance to ensure good coordination between the village head, village officials, and the community. The research method used is qualitative research with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the communication strategies implemented in Ciburuy Village are quite effective in improving the performance of village officials. Some of the communication methods used include regular meetings, the use of WhatsApp groups, the